Building a Local Preservation Ethic in the Era of Urban Renewal: How Did Neighborhood Associations Shape Historic Preservation Practice in Lexington, Kentucky?. (March 2020) - Poole, Lauren A. R.; Appler, Douglas R.
The federal urban renewal program had wide-ranging consequences for American cities of all sizes and locations. Among the most consequential was its catalyzing effect on the historic preservation movement nationwide. While preservation practice at the dawn of the urban renewal era emphasized historic monuments, by its end in the mid-1970s, preservationists were much more concerned with neighborhoods, districts, and larger swaths of urban fabric, thus, becoming relevant to all manner of future city shaping and revitalizing efforts. While this expansion took place nationwide, the paths taken by individual cities varied considerably. Because of its large number of historic downtown residential neighborhoods, and its long involvement with historic preservation, Lexington, Kentucky, provides an ideal case study to explore this transformation, highlighting the ways in which neighborhood associations and local preservation organizations collaborated to set the stage for widespread adoption of local historic districts in the 1970s.